Agreement between the Danish Cancer Registry and the Danish Colorectal Cancer Group Database. (2nd January 2020) - Christensen, Jane; Højsgaard Schmidt, Lise Kristine; Kejs, Anne Mette Tranberg; Søgaard, Jes; Rasted, Margit Caroline; Andersen, Ole; Ingeholm, Peter; Iversen, Lene Hjerrild
Abstract: Background: The Danish Cancer Registry (DCR) and the Danish Colorectal Cancer Group (DCCG) database are population-based registries collecting information on Danish patients with colorectal cancer (CRC). DCR registers all patients with incident CRC whereas DCCG records patients with first time CRC. The registries use different inclusion criteria. The consequencenses of this are unknown and not previously evaluated. The aim of this study was to examine the agreement between patients registered in DCR and DCCG and to evaluate its influence on estimated survival and mortality. Material and methods: Patients registered in DCR and DCCG with CRC in 2014–2015 were included. Because of different inclusion criteria, DCCG's inclusion criteria were applied to DCR. Descriptive statistics were used for comparisons. One-year relative survival (1-year RS) was calculated, and the Cox proportional hazard model used for calculating 1-year mortality rate ratios (1-year MRR). Results: In 2014–2015, DCR registered 9678 Danish residents with CRC that fulfilled DCCG's inclusion criteria, while DCCG registered 10, 312 Danish residents with CRC. Allowing ±180 days between dates of diagnosis, 10, 688 patients were registered with CRC in the merger of the two registries. Of these, 86% were included in both registers, 4% only in DCR, and 10% only in DCCG. No difference was found in 1-year RS between patients in DCR 86% (95% CI: 85–87) and DCCG 85% (95% CI: 84–86). However, patients registered in DCCG had a 1-year MRR of 1.09 (95% CI: 1.01–1.17) compared to DCR. Conclusion: An agreement of 86% of patients was found between the two registries. The discrepancy did not influence 1-year RS. DCCG registered more patients than DCR, and 1-year MRR of patients in DCCG was increased compared to patients in DCR. Regular linkage of the registries is recommended to improve data quality of both registries.